Irisin may have a role in pubertal development and regulation of reproductive function in rats - Ulker, Nazife; Yardimci, Ahmet; Tektemur, Nalan Kaya; Bulmus, Ozgur; Kaya, Seyma Ozer; Bulmus, Funda Gulcu; Canpolat, Sinan (Bioscientifica Ltd, 2020)
Physical exercise and body muscle/fat mass are known to affect the endocrine system, puberty onset and reproductive health. However, the potential effects of irisin, an adipo-myokine and exercise-induced hormone, have not yet been fully elucidated on reproductive maturation. Therefore, the present study aimed to determine the effects of irisin administration on pubertal maturation and reproductive system in female and male rats. Daily i.p. injection of irisin (100 ng/kg; from postnatal day 21 for about 10 weeks) delayed the ages at the vaginal opening (as an external index of puberty onset) and first estrus. Furthermore, continuous administration of irisin to female rats caused a significant decrease in serum follicle-stimulating hormone levels and an increase in serum luteinizing hormone and 17 beta-estradiol levels, as well as causing histopathological changes in the ovarian tissue. On the contrary, irisin administration to male rats did not modify the timing of puberty, as estimated by age at preputial separation. However, chronic exposure to irisin produced significant increases in serum luteinizing hormone and testosterone levels and also sperm concentration and seminiferous tubule diameter in male rats. In conclusion, irisin exposure has different effects on both pubertal maturation and reproductive system in female and male rats. The present findings reveal that chronic irisin exposure may lead to disorders in the female reproductive system and may have androgenic potential on the hypothalamic-pituitary-gonadal axis in males.
Keywords: Sprague-Dawley Rats; Circulating Irisin; Physical-Activity; Gene-Expression; Prostate-Cancer; Protective Role; Exercise; Testosterone; Hormone; Fat